Zadunajscy przesiedleńcy (Gagauzi oraz Bułgarzy) w południowej Besarabii - uwarunkowania polityczno-historyczne - Hatłas, Jerzy (Pikktor, 2010)
The Bessarabia is a territory located between the rivers of Prut and Dniester. It's southern part, (at times referred to as Budjak) is a true ethnic mosaic. It's inhabited by Ukrainians, Russians, Bulgarians, Gaugasians, Albanians as well as representatives of other nations. Currently, the territory is divided into two states (Moldova and Ukraine). Much of the area of southern Bessarabia is characterized by compact Bulgarian-Gaugasian settlements. Both these ethnos' have arrived here as emigrants from not distant Balkans (area of contemporary Bulgaria). In Southern Moldova the Gaugasians have received autonomy. In December 1994 the Autonomous Territorial Unit of Gägäuzia (Gagauz Yeri) was established. The majority of the territory is within the Moldavian borders. The situation is very different with regard to Bulgarians who mostly inhabit the south-eastern part of the Ukrainian Odessa region and hardly enjoy any autonomy. The unofficial capital of the Bulgarians that live in the Bessarabia is the city of Comrad. The Bulgarians in the Ukraine (mostly located in Southern Bessarabia) constitute the biggest Bulgarian diaspora in the world. Owing to massive resettlement processes which originate from the XVIIIth century, and which have continued throughout the XXth century the Southern Bessarabia has witnessed the rise of numerous multi-ethnic municipalities in which the Danube emigrants (Bulgarians and Gaugasians in particular) constitute not a minority, but a majority of the citizens.
The danube emigrants (Gaugasians and the Bulgarians) in southern Bessarabia - social and political environment
Keywords: Gagauzi; Bułgarzy; Besarabia; uwarunkowania polityczno-historyczne